Evaluasi Aksesibilitas Fisik Masjid dan Fasilitas Pendukung Untuk Difabel Pada Masjid-Masjid Perumahan di Sleman - Rafi Malaika Rayhan; M. Galieh Gunagama; Yasyvieni Nooranita (Universitas Muslim Indonesia, 2024)
This study examines the evaluation of physical accessibility and supporting facilities for people with disabilities in two residential mosques in Sleman, Yogyakarta, Indonesia. The mosques in focus are Masjid Khusnul Khatimah and Masjid Jami' At-Taqwa, chosen to assess the extent of accessibility and availability of supporting facilities for people with disabilities. The research method used is qualitative descriptive, with data collection through observation and interviews with two mosque managers, two people with disabilities, and four general worshipers. The results show that mosques in Sleman still face challenges in terms of physical accessibility and supporting facilities for people with disabilities. However, there are also positive responses from mosque managers in improving accessibility and comfort for people with disabilities, such as providing facilities like ramps, handrails, adjustments to the height of stairs, and replacing slippery materials at entrance areas. Additionally, mosques also serve educational, social, and economic functions that need to be considered in evaluating physical accessibility. With this evaluation, residential mosques in Sleman are expected to become more inclusive and friendly for people with disabilities